2010
DOI: 10.1016/j.foreco.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The influence of partial timber harvesting in riparian buffers on macroinvertebrate and fish communities in small streams in Minnesota, USA

Abstract: a b s t r a c tRelatively few evaluations of aquatic macroinvertebrate and fish communities have been published in peer-reviewed literature detailing the effect of varying residual basal area (RBA) after timber harvesting in riparian buffers. Our analysis investigated the effects of partial harvesting within riparian buffers on aquatic macroinvertebrate and fish communities in small streams from two experiments in northern Minnesota northern hardwood-aspen forests. Each experiment evaluated partial harvesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…First, the decrease in canopy cover was minimal at Pine and Bailey Creeks (9 % and 7 % decrease, respectively). Previous studies with similar reductions in canopy cover also found no temperature response [36,66,81,82]. Second, there was still a substantial amount of canopy cover remaining at Pine Creek (55 %), Bogard Creek (39 %), and Bailey Creek (45 %) which likely provided sufficient shading to continue to moderate stream temperature.…”
Section: Resultsmentioning
confidence: 75%
“…First, the decrease in canopy cover was minimal at Pine and Bailey Creeks (9 % and 7 % decrease, respectively). Previous studies with similar reductions in canopy cover also found no temperature response [36,66,81,82]. Second, there was still a substantial amount of canopy cover remaining at Pine Creek (55 %), Bogard Creek (39 %), and Bailey Creek (45 %) which likely provided sufficient shading to continue to moderate stream temperature.…”
Section: Resultsmentioning
confidence: 75%
“…The changes in the avian community following timber harvesting within RMZs differed from the macroinvertebrate and fish communities under the same treatments in our experimental sites (Chizinski et al, 2010). Although harvesting to the low RBA was adequate in minimizing the effect on the aquatic system, there was indication of disruption to the avian community (this study).…”
Section: Discussionmentioning
confidence: 57%
“…Preservation of riparian forests along streams is better than complete deforestation, but this preservation effort is insignificant compared to nonharvested areas because the reduction in litter still leads to fewer shredders (Lecerf & Richardson 2010). When harvesting occurs in areas that are less than 200 m long, no effect of riparian buffer forest harvest on aquatic insects is detected (Chizinski et al . 2010).…”
Section: Deforestationmentioning
confidence: 99%